USE OF LEARNING MEDIA IN FORM PLATFORM LINK AT THE COLLEGE OF TARBIYAH SCIENCE OLD PADANG OF OLD MOUNTAIN - Ahmad Ihsan Pardamean Siregar; Irpan Haj Siagian; Zulhimma (PT. Jurnal Center Indonesia Publisher, 2026)
This research examines the implementation and effectiveness of using learning media in the form of link platforms for students at the Islamic Education College (STIT) Padang Lawas Gunung Tua as a form of Community Service (PKM). This activity aims to improve digital literacy and pedagogical technology competence of students as prospective educators in the digital era. The implementation method involved 3rd and 5th semester students through two intensive training sessions that included concept presentations, technical demonstrations, and hands-on practice in creating link platform-based learning media such as Google Sites, Canva, and simple Learning Management Systems (LMS). Evaluation results show that this training successfully improved students' understanding of technology concepts and applications in learning. There was an increase in practical skills in managing digital content, creating interactive media, and integrating multimedia in one easily accessible platform. Students also demonstrated new awareness about the importance of digital literacy and ethics in using online content. Additionally, a commitment emerged to apply these skills in future teaching practices. It is concluded that this hands-on practice-based training is effective in strengthening students' pedagogical technology competencies while also contributing positively to developing the quality of prospective educators at STIT Padang Lawas Gunung Tua. Similar sustainable activities with intensive mentoring are recommended to strengthen impact and build a sustainable digital learning ecosystem.